Statistical Methods for Sustainability Measurement of Supply Chain Management - Khosravi, Faramarz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Sustainability is of essential interest for many organizations and is defined as the ability to maintain existing resources at a certain rate or level when encountered with barriers. Factors affecting sustainability are categorized as enablers (capacities) and barriers (challenges) that have positive and negative effects on sustainability, respectively. To evaluate the status of sustainability, organizations need a measurement method to account for all the aspects of the sustainability classified into social, economic, and environmental tiers. Previously, many researchers have provided indicators for measuring sustainability in specific fields, which is not applicable to organizations operating in other areas. The main purposes of this research are to investigate how statistical methods are used to improve previous methods of sustainability measurement as well as to propose a new approach to sustainability measurement at organizational and supply chain management (SCM) levels. Emphasis is particularly devoted to determining how the sustainability of supply chains may be measured in the presence of exponentially distributed indicators for both independent and dependent variable cases.

ÖZ: Sürdürülebilirlik birçok kuruluş için büyük önem taşımakta ve mevcut kaynakların engellerle karşılaşıldığında belirli bir oranda veya seviyede korunabilmesi becerisi olarak tanımlanmaktadır. Sürdürülebilirliği etkileyen faktörler, sürdürülebilirlik üzerinde olumlu ve olumsuz etkileri olan kolaylaştırıcılar (kapasiteler) ve engeller (zorluklar) olarak sınıflandırılmıştır. Sürdürülebilirliğin durumunu değerlendirebilmek için, kuruluşların, sürdürülebilirliğin sosyal, ekonomik ve çevresel katmanlarda sınıflandırılan tüm yönlerini hesaba katacak bir ölçüm yöntemine ihtiyaçları vardır. Daha önce yapılan çalışmalarda araştırmacılar, her alanda faaliyet gösteren kuruluşlara değil, sadece üzerinde çalışılan alanda uygulanabilecek sürdürülebilirlik göstergeleri önermişlerdir. Bu araştırmanın temel amaçları, önceki sürdürülebilirlik ölçüm yöntemlerini geliştirmek için istatistiksel yöntemlerin nasıl kullanıldığını araştırmanın yanı sıra, organizasyonel ve tedarik zinciri yönetimi (SCM) düzeylerinde sürdürülebilirlik ölçümüne yeni bir yaklaşım önermektir. Özellikle üzerinde durulan nokta, üstel olarak dağıtılmış göstergelerde bağımsız ve bağımlı değişkenlerin her ikisi için de tedarik zincirlerinin sürdürülebilirliğinin nasıl ölçüleceği ile ilgilidir.
Doctor of Philosophy in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2020. Supervisor: Assoc. Prof. Dr. Gökhan İzbırak
Keywords: Industrial Engineering Department; Statistical Performance Measurement, Bootstrap Re-sampling, AHP, TBL (Triple Bottom Line), Independent and Dependent Exponentially Distributed Indicators, Supply Chain Stakeholders, Copula Function; Supply Chain Management; Production Management